Pengabdian Masyarakat Diaplikasikan dalam Yayasan Darul Falah Tulungrejo Pare Kediri - Azizah, Salsa Nur; Bagas, Mafaza; Suryanto (Indra Institute Research & Publication, 2024)
This service aims to analyze the role of the Darul Falah Al-Qur'an Education Park (TPQ) in Tulungrejo Village, Pare, Kediri in forming the character of students through mentoring, continuous training and advice in forming religious, independent and communicative character in children through learning activities and internalization of Islamic values. TPQ plays an important role through habituation activities to foster positive religious character from an early age based on Islamic teachings. Achieving success in learning depends on the material presented and the methods used in learning. But in this case it is definitely not an easy thing. The problem in this case is the lack of human resources and the lack of consistency when implementing learning methods.